A giant landslide-explosion circue and debris avalanche at Bakening volcano, Kamchatka - Melekestsev I.V.; Dirksen O.V.; Girina O.A. (My University, 1999)
This study revealed that the giant cirque of Bakening Volcano had been produced by its eruption ca. 8000-8500 carbon-14 year ago. The eruption is supposed to have been heralded by a large earthquake (M > 7) resulting in the collapse and slide of the SE sector of the cone. The landslide unroofed the hydrothermal system and triggered an explosion which was followed by an ash-and-block pyroclastic flow. A rockslide avalanche rolled down into the valley of the Srednyaya Avacha River and travelled as far as 10-11 km along it. The avalanche deposited its debris material over an area of 18-20 km2 measuring 0.4-0.5 km3 in volume. These deposits dammed the river, produced two lakes (Bezymyannoe and Verkhneavacha), and gave birth to a large lahar which traveled along the valley much farther.
Keywords: 38.37.25 Вулканология; Бакенинг